TEKNIK PENGAMANAN PESAN DENGAN ALGORITMA RC4 DAN METODA LSB - J. Bendi, R. Kristoforus; Budiman, Erwin (Proceedings of KNASTIK, 2012)
information. By using various techniques, many people are trying to accessinformation that they are should not have access to. With the development ofscience, the application of information security techniques and data that have beenused in ancient times can be an alternative in securing datacommunications. Cryptography is a science and art to maintain the security ofmessages sent from one place to another. RC4, one cryptographic algorithm, is widelyapplied to encrypt information. Cryptography can still be broken even if the processtakes time, cost and effort. Other data security techniques are also quite popular issteganography. In contrast to cryptographic techniques, steganography can reducesuspicion because the message is disguised is hidden in another file. LSB is one ofsteganographic methods. LSB widely applied to insert a secret message into a digitalimage.This software is made in order to secure the secret message into a digital imageusing the RC4 algorithm and the method of LSB. The software is built using thewaterfall model of software development.The results of the development of this softwarehas been able to secure the secret message in the form of text into a digital image witha BMP format using RC4 algorithm and the method of LSB.